Regen - Ivens, Joris (Netherlands, 1929)
3 versions of 15 or 12 minutes. Co-director Mannus Franken.
Joris Ivens, Wereldcineast. DVD 1, 1912/1933. Musical scores by Lou Lichtveld (1932), Hanns Eisler (1941) or the Lichtveld score newly recorded (2002).
Duration: 00:15:00